Consistency of explicit and implicit self-esteem in individuals with narcissistic disorders - Anastatia Kovalinas, (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2015)
This article deals with the psychophysiological characteristics of the narcissistic person; the self-esteem with the narcissistic personality disorder; and the discrepancies between implicit and explicit self-esteem. It found the relationship between narcissism and self-esteem, which allows exploring aspects of its impact on the severity of the disorder.
Keywords: narcissistic personality disorder; explicit and implicit self-esteem; Self-system